2019
DOI: 10.1016/j.jare.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

NiSn nanoparticle-incorporated carbon nanofibers as efficient electrocatalysts for urea oxidation and working anodes in direct urea fuel cells

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Therefore, generating hydrogen from urea-polluted wastewater solves an environmental problem simultaneously. Theoretically, production of hydrogen from urea does not need additional power, as it is an exothermic reaction according to the following equations [17][18][19][20] So far, based on our best knowledge, no anode material has been reported that could achieve the task without additional power.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, generating hydrogen from urea-polluted wastewater solves an environmental problem simultaneously. Theoretically, production of hydrogen from urea does not need additional power, as it is an exothermic reaction according to the following equations [17][18][19][20] So far, based on our best knowledge, no anode material has been reported that could achieve the task without additional power.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, the onset potential, an important parameter to be extracted from CV experiments was about 30 mV less positive on 3-Ni/CF (0.47 V) than on 6-Ni/CP and 12-Ni/CP. The decrease of the onset potential is related to a change in the required activation energy for the process, and a suitable catalyst enhances the reaction rate by decreasing the activation energy [46]. It is important to point out that the onset potential starts at the similar potential of the conversion from Ni 2+ to Ni 3+ , confirmed that NiOOH is the active phase for the urea electro-oxidation reaction [37,38].…”
Section: Resultsmentioning
confidence: 85%
“…The stability of the catalyst is also demonstrated by the minor loss of current density after 1000 CV cycles (Figure g). Apart from the above‐two detailed discussed examples, other notable studies on DUFC catalysts include NiMn‐decorated activated carbon, Se‐Ni(OH) 2 ‐shelled NiSe nanowires, NiSn nanoparticle‐incorporated carbon nanofibers, and NiCo‐decorated carbon nanotubes . Their catalytic performance is summarized in Table 3 .…”
Section: Direct Urea Fuel Cellsmentioning
confidence: 99%